Hydrogen-bonded macrocycle-mediated dimerization for orthogonal supramolecular polymerization - Wentao Yu; Zhiyao Yang; Chengkan Yu; Xiaowei Li; Lihua Yuan (Beilstein Journal of Organic Chemistry)
Orthogonal self-assembly represents a useful methodology to construct supramolecular polymers with AA- and AB-type monomers, as commonly used for covalently linked polymers. So far, the design of such monomers has relied heavily on three-dimensional macrocycles, and the use of two-dimensional shape-persistent macrocycles for this purpose remains rather rare. Here, we demonstrate a dimerization motif based on a hydrogen-bonded macrocycle that can be effectively applied to form orthogonal supramolecular polymers. The macrocycle-mediated connectivity was confirmed by single-crystal X-ray diﬀraction, which revealed a unique 2:2 binding motif between host and guest, bridged by two cationic pyridinium end groups through π-stacking interactions and other cooperative intermolecular forces. Zinc ion-induced coordination with the macrocycle and a terpyridinium derivative enabled orthogonal polymerization, as revealed by 1H NMR, DLS, and TEM techniques. In addition, viscosity measurements showed a transition from oligomers to polymers at the critical polymerization concentration of 17 μM. These polymers were highly concentration-dependent. Establishing this new dimerization motif with shape-persistent H-bonded macrocycles widens the scope of noncovalent building blocks for supramolecular polymers and augurs well for the future development of functional materials.